MODEL PERTUNJUKAN BARONGAN ANAK SEBAGAI TRANSMISI BUDAYA DAERAH - Karyono, K.,; Slamet, S.,; Mulyadi, Tubagus (Acintya, 2015)
This research represents an action research that put the data as a material processing for research activities as a performance model of BaronganAnak (kids Barongan). Barongan is one of the folk arts that havetaken root in Blora. It is related to their belief that Barongan is reputed to protect and it can be seen in the ritual ceremony Lamporan. During this time, Barongan is presented in procession for ritual as well as national ceremony. After watching the kids play Barongan and imitateBarongan movements, there appears an idea to do research and to design a performance model of the Barongan Anak. The performance model needs to be introduced to the society in order to make regeneration and conserving local cultures. The method used in the research is experimentation and formation. Experimentation method is used to seek the alternative of performance model and the formation method is used to make a model.Keywords: model, kids Barongan, transmission system, inheritance.